Periplaneta americana extract promotes intestinal mucosa repair of ulcerative colitis in rat - Xue,Nan-nan (2020)
Abstract Purpose: To investigate the mechanism of Periplaneta americana extract promoting intestinal mucosal repair of OXZ-induced colitis in rat. Methods: All experiments used an equal number of male and female SD rats (n=48). We injected OXZ into the colon to induce UC rat model. To determine the optimal concentration of P. Americana's extract (PA-40), it was classified into low (L), medium (M), and high (H) doses. After OXZ treatment, each drug was administered by enema for 7 consecutive days. Rats were divided into the following 6 groups: (1) Saline treatment group (NC), (2) OXZ treatment UC model group (MC), (3) OXZ + budesonide group (BUN), (4) OXZ + PA-40 L group, (5) OXZ + PA-40 M group, (6) OXZ + PA-40 H group. Disease activity index (DAI) scores, colon length, histopathological score, serum cytokine level (IL-4, IL-10, iNOS, tNOS), and amount of MPO, EGF, IL-13 in colonic mucosa were measured. Results: PA treatment had a significant healing effect on the OXZ-colitis model and significantly reduced the lesioned area, especially in the PA-40H groups. PA treatment did not alter the expression of IL-10 and MPO level, but increased EGF (epidermal growth factor) and decrease IL-13 in the colonic tissue. PA inhibited the rise of NOSs (nitric oxide synthase) and decreased the serum IL-4 level. Conclusions: The data suggest that Periplaneta americana extract may be a potential compound for the treatment of colonic lesions. The mechanism may be related to inhibiting the secretion of IL-13 and promoting the formation of EGF.